E-135 Effect of balloon guide catheter on self-reported angiographic outcomes in mechanical thrombectomy: a survey analysis. (22nd July 2018) - Mehta, T; Male, S; Tore, H; David, K; Siddiqui, A; Turk, A; Grande, A; Tummala, R; Jagadeesan, B
Abstract : Introduction: Mechanical thrombectomy is a highly effective treatment of large vessel occlusion ischemic strokes. There are wide variations in the techniques of thrombectomy depending on providers or institutional preference. Recent trials suggest that use of balloon guide catheters (BGC) leads to better recanalization rates. Hereby, we attempt to evaluate the effect of BGC on self-reported angiographic outcomes. Methods: An 18-questionnaire survey was designed using Qualtrics software available through our institution. The survey questions were aimed to extract the information regarding various techniques of thrombectomy, use of BGC during these techniques and self-reported angiographic outcomes. The survey allowed individual practitioners to respond while maintaining complete anonymity. After obtaining institutional review board (IRB) approval, the survey link was posted on Society of Neurointerventional Surgery (SNIS) website in 'SNIS Connect', an exclusive member-only forum of SNIS. Results: Over a period of 2 weeks, 70 responses were obtained that were included in final analysis. 16 (22.9%) out of 64 respondents (6 missing) reported preferring the use of BGC during thrombectomy. Of these, 6 (37.5%) were Neuroradiologists, 4 (25%) were Neurosurgeons, 4 (25%) were Neurologists and 2 (12.5%) identified themselves as other. The BGC use was most common during 7 (43.8%) stentretriever without aspiration technique followed by 6 (37.5%) Solumbra technique and 3 (18.8%) ADAPT technique. Self reported successful recanalization defined as >80% TICI 2B and TICI 3 was found in 7 (43.8%) in BGC group versus 40 (85.1%) in non-BGC group (p=0.001). After adjusting for operator experience, volume of procedures and background training; self reported successful recanalization defined as >80% TICI 2B and TICI 3 was still higher in non-BGC group compared to BGC group (Odds ratio 9.577, p=0.037). Conclusion: The study reveals paradoxical findings of poorer self-reported angiographic outcomes with the use of BGC. This directly contradicts the results of prior clinical trials. Disclosures: T. Mehta: None. S. Male: None. H. Tore: None. K. David: 1; C; Medtronic, MicroVention, NeuroSigma, Shape Memory Therapeutics, IndumedX, Sequent Medical, Neurogami, and NeuroSave. 2; C; Consulting for Medtronic (all funds to the institution); ownership stake in Marblehead Medi. A. Siddiqui: 1; C; Codman and Shurtleff LARGE Aneurysm Randomized Trial, Covidien (now Medtronic) SWIFT PRIME and Solitaire With the Intention For Thrombectomy Plus Intravenous t-PA Versus DIRECT Solitaire Stent-retriever. 2; C; Amnis Therapeutics Ltd., Cerebrotech Medical Systems Inc., Cerenovus (formerly Codman Neurovascular, Neuravi, and Pulsar Vascular), CereVasc LLC, Claret Medical Inc., Corindus Inc., GuidePoint Global. 3; C; Apama Medical, Buffalo Technology Partners Inc., Cardinal Health, Endostream Medical Ltd., International Medical Distribution Partners, Medina Medical Systems, Neuro Technology Investors, StimMed, Val. A. Turk: 1; C; Medtronic, Penumbra, MicroVention, and Stryker. 2; C; Medtronic, Penumbra, MicroVention, and Stryker. A. Grande: None. R. Tummala: None. B. Jagadeesan: 1; C; Microvention, Medtroni. 2; C; Microvention, CvRx.